(untitled) (Microbes and Health, 2014)
Fish is known to harbour bacteria of public health importance. Aquatic environments of ponds are known to influence the bacterial loads of the harvested fish. The present work was undertaken to determine total viable count (TVC) and isolation and identification of bacteria from Koi fish, mud and water samples of two selected ponds managed and owned by the Bangladesh Fisheries Research Institute (BFRI) and two ponds located at Muktagacha, Mymensingh, managed by private owners. Fish (n=16), mud (n=16) and water (n=16) samples were collected from all 4 ponds. Samples were cultured on plate count agar to determine TVC. Fish harvested from Muktagacha ponds had statistically higher bacterial count (8.44 ± 0.04 log10 CFU/ml) when compared to BFRI ponds (7.92±0.17 log10 CFU/ml) (p? 0.05). Similarly, highest TVC was found in mud and water samples of Muktagacha ponds (6.87±0.73 and 7.41±0.04 log10 CFU/ml, respectively) compared to mud and water samples of BFRI ponds (5.04 ±0.07 and 5.40±0.09 log10 CFU/ml, respectively). Samples were inoculated onto appropriate selective media for isolation of bacteria. Total 257 bacterial isolates representing five genera were identified: Pseudomonas spp. (21.40%), Aeromonas spp. (33.46%), Vibrio spp. (14.78%), Salmonella spp. (21.40%) and E. coli (8.94%). Antibiotic sensitivity assay showed multidrug resistant profiles of Pseudomonas sp., Aeromonas sp., Salmonella sp. and E. coli. These bacteria are known to cause food borne illness in humans and spoilage of fish. Microbes and Health, June 2013, 2(1): 8-11 DOI: http://dx.doi.org/10.3329/mh.v2i1.17255